2019
DOI: 10.1177/0333102418815503
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of cluster headache

Abstract: Background Cluster headache is the most severe primary headache disorder. A genetic basis has long been suggested by family and twin studies; however, little is understood about the genetic variants that contribute to cluster headache susceptibility. Methods We conducted a literature search of the MEDLINE database using the PubMed search engine to identify all human genetic studies for cluster headache. In this article we provide a review of those genetic studies, along with an overview of the pathophysiology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 110 publications
1
31
1
1
Order By: Relevance
“…Knowledge of the primary headaches comes largely from the work in the most prevalent disorders, namely tensiontype headache, migraine, and cluster headache. This supports the concept that these disorders occur in those genetically predisposed [2][3][4] and, where the inherent pathology is in the central nervous system. When individuals first experience a headache, the concern is often about a sinister precipitating pathology [5].…”
Section: Introductionsupporting
confidence: 83%
“…Knowledge of the primary headaches comes largely from the work in the most prevalent disorders, namely tensiontype headache, migraine, and cluster headache. This supports the concept that these disorders occur in those genetically predisposed [2][3][4] and, where the inherent pathology is in the central nervous system. When individuals first experience a headache, the concern is often about a sinister precipitating pathology [5].…”
Section: Introductionsupporting
confidence: 83%
“…The hypothalamus is also reported to be activated during a CH attack, a possible explanation for the rhythmic pattern with which the symptoms occur during active periods [8,9]. The cause of CH is currently unknown, but several studies suggest that genetic factors contribute to the risk of developing the disorder [10]. Genetic associations with CH have today been reported for several candidate genes [11,12,13,14,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…However, heritability of the TACs is not proven by this fact. Several studies showed no major genetic risk for TACs (8), although a higher familial risk has been shown in epidemiological studies (1). It seems unlikely that environmental factors or social/observational learning can induce TACs in these very young patients.…”
Section: Discussionmentioning
confidence: 99%